Effect Of Debt To Equity Ratio, Price Earning Ratio And Price To Book Value On Stock Returns In The Company PT. Bank Cimb Niaga Tbk Period 2013-2022 - Hasanah; Kusumawardhani , Aninditha Putri; Sarifiyono , Aggi Panigoro (Journal of Business and Management Inaba, 2023)
This research aims to determine the description and influence of Debt to Equity ratio, Price Earning Ratio, and Price to Book Value on Stock Returns. The object of this research is PT Bank CIMB Niaga Tbk, the method used is descriptive and verification methods with a quantitative approach. The population in this study were ten financial reports of PT Bank CIMB Niaga Tbk for the 2013-2022 period using a sampling technique, namely non-probability sampling, a saturated sample type. The results of this research show that the Debt-to-Equity Ratio, Price Earning Ratio, Price to Book Value, Stock Returns fluctuate, tend to decrease, and are below standard. Based on the results of the determination test, it is known that partially the influence of the Debt-to-Equity Ratio is 13.4%, the influence of the Price Earning Ratio is 5%, the influence of Price to Book Value is 15.7% and the influence of the Debt-to-Equity Ratio, Price Earning Ratio and Price to Book Value simultaneously affect share returns of 58.8%.